2008
DOI: 10.1177/0731684407082629
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Corrosion Behavior of AA7075 Al/SiCP and Al/Al2O3 Composites Fabricated by Powder Metallurgy

Abstract: In this investigation an attempt has been made to fabricate Al-SiC p and Al-Al2O3 composite materials by powder metallurgy technique at different volume percentage of reinforcement (5, 10, 15, 20, and 25%). The corrosion behavior of the composites were analyzed using AC Gill potentiostat with 3.5 wt% NaCl medium. Four factor, five level, central composite, rotatable design matrix is used to optimize the required number of experiments. The mathematical models were developed by the response surface method (RSM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This may be due to that the microstructure of the spray deposited MMC is compact and SiC particles are nonmetallic material, the addition of it minimizes the real corrosion area of the alloy. In another study [62], an attempt has been made to fabricate Al-SiC p and Al-Al 2 O 3 composite materials by powder metallurgy technique at different volume percentage of reinforcement (5,10,15,20, and 25%). The corrosion behavior of the composites was analyzed using AC Gill potentiostat with 3.5 wt% NaCl medium.…”
Section: The Recent Past [Since 2000]mentioning
confidence: 99%
“…This may be due to that the microstructure of the spray deposited MMC is compact and SiC particles are nonmetallic material, the addition of it minimizes the real corrosion area of the alloy. In another study [62], an attempt has been made to fabricate Al-SiC p and Al-Al 2 O 3 composite materials by powder metallurgy technique at different volume percentage of reinforcement (5,10,15,20, and 25%). The corrosion behavior of the composites was analyzed using AC Gill potentiostat with 3.5 wt% NaCl medium.…”
Section: The Recent Past [Since 2000]mentioning
confidence: 99%
“…The corrosion rate of each specimen was recorded and the values of corrosion fell between 1.31 and 8.231 mm/year. The modeling and optimization of the specimens were discussed elsewhere [10].…”
Section: Conducting the Experimentsmentioning
confidence: 99%
“…If corrosion potential is more positive, pitting corrosion is initiated in aluminium alloy matrix. Mathematical models can be used for the prediction of accurate results [9]. Abhishek Sharma et al reported that Al6061-SiC-graphite hybrid surface composite has an improved corrosion resistance property due to the decrease of interfacial corrosion.…”
Section: Introductionmentioning
confidence: 99%